Coupling effects of the electric field and bending on the electronic and magnetic properties of penta-graphene nanoribbons. Issue 28 (5th July 2017) - He, C.; Wang, X. F.; Zhang, W. X.
Abstract : The magnetic configuration transitions for P-GNRs vs. critical electric field strength on applying different bending strains. Abstract : Quasi one-dimensional materials made from carbon have attracted a lot of attention because of their interesting properties and potential applications in electronic devices. Recently, new kinds of carbon allotropes named as penta-graphene nanoribbons (P-GNRs) have been proposed. By implementing first-principles calculations, P-GNRs exhibit large tunable band gaps under bending stress, and the band gaps of P-GNRs are easier to control than those of GNRs. In addition, the order of spin moments of P-GNRs can transform from ferromagnetic to antiferromagnetic under the coupling effect of the electric field and bending strain, thus resulting in a significant change of magnetism. Therefore, the diverse electronic and magnetic properties highlight the potential applications of P-GNRs in flexible displays, wearable computation electronics and digital memory devices.